Low-smoke halogen-free flame-retardant polyolefin insulating material for in-vehicle high-voltage cable and preparation method thereof
By using non-oil-filled SEBS, ethylene-propylene-butene block copolymer elastomer and polyethylene grafted maleic anhydride as matrix resins in high-voltage cable materials in new energy electric vehicles, and using phospho-containing silane modified hydroxide oxidation As flame retardants, aluminum and polycarbosilane combined with 5 or 6 functional group cross-linking sensitizers solve the problem of degradation in the material under high temperature and irradiation conditions, and achieve efficient flame retardant and tear resistance.
Patent Information
- Application Number
- CN202411306935.2
- Authority / Receiving Office
- CN · China
- Patent Type
- Applications(China)
- Current Assignee / Owner
- Filing Date
- 2024-09-19
- Publication Date
- 2025-02-07
- Estimated Expiration
- 2044-09-19
AI Technical Summary
The prior art has shortcomings in improving the oil resistance, flame retardant performance, flexibility and tear resistance of high-voltage cables in new energy electric vehicles, especially in high temperature environments and irradiation conditions, the mechanical and electrical properties of the materials are easy to be decline.
Non-oil-filled SEBS, ethylene-propylene-butene block copolymer elastomer and polyethylene grafted maleic anhydride as matrix resins, and ultrafine aluminum hydroxide and polycarbonsilane modified as flame retardants are used. , combined with 5 or 6 functional group cross-linking sensitizers, improve the flame retardant and tear resistance of the material.
The excellent oil resistance, flame retardant properties, softness and tear resistance of high-voltage cable materials are achieved, and good mechanical and electrical properties can be maintained under high temperature and irradiation conditions, reducing the risk of material aging and performance degradation.
Smart Images

Figure BDA0005049503430000031 
Figure BDA0005049503430000041 
Figure BDA0005049503430000042
Abstract
Description
Technical Field
[0001] The low-smoke halogen-free flame-retardant polyolefin insulation material for in-vehicle high-voltage cables proposed by the present invention is applied to the field of new energy electric vehicles and has excellent oil resistance, flame retardancy, flexibility and tear resistance. Background Art
[0002] At present, the global new energy electric vehicles are developing rapidly, and people have higher requirements for electric vehicles, such as pursuing higher endurance, faster acceleration and faster charging speed, which puts higher requirements on automotive supporting components. However, there are also many problems, and quality problems have repeatedly occurred. In addition, consumers have put forward higher requirements for the endurance and speed of electric vehicles. The implementation of these requirements cannot be separated from the support of high-quality and high-performance wires and cables inside electric vehicles. At present, new energy vehicles are mainly divided into pure electric and oil-electric hybrid. The wires and cables connecting various components inside the car need to have higher performance. It is necessary to prevent the cracking of wires and cables and the decrease of material insulation electrical performance after impregnation with chemical reagents, thereby causing short circuit fire. In order to reduce the incidence of fire and the mortality rate when fire occurs, higher requirements are also put forward for the flame retardant performance of cables. In addition, the higher endurance requirements of new energy electric vehicles mean that the installed capacity of electric vehicles will increase, the space occupied by batteries will be larger, and the installation space of high-voltage wiring harnesses will be further reduced, which also puts forward higher requirements for the overall softness of materials.
[0003] Defects and shortcomings of the existing technology:
[0004] 1. Chinese patent application CN 117659558A proposes a low-smoke, halogen-free, highly flame-retardant cable material for high-voltage lines in new energy vehicles and its preparation method. This material for high-voltage soft cables in vehicles uses an oil-resistant modified resin to improve the oil resistance and softness of the material. The resin contains polyphenylene ether material. Since polyphenylene ether has a high melting point, aluminum hydroxide is added as a flame retardant in this solution. According to literature and actual use experience, when the extrusion processing temperature is higher than 200°C, aluminum hydroxide begins to dehydrate, which will seriously affect the extrusion processing of the material, causing pores and resulting in a decrease in the mechanical and electrical properties of the material. The melting point of polyphenylene ether is higher than 200°C. When it is lower than the melting point, polyphenylene ether is difficult to disperse evenly, which can easily cause the material to crack in the later stage. In order to improve the softness of the material while taking into account the flame retardant properties, this solution uses hydromagnesite and aluminum hydroxide / aluminum hypophosphite as the main flame retardants. At the same time, graphite black and carbonizing agents need to be introduced to meet the relevant flame retardant requirements and softness. Aluminum hypophosphite is acidic and alkaline, and hydromagnesite is easy to react, affecting the extrusion process. At the same time, the introduction of graphite black limits its application range (currently most of the high-voltage cables in vehicles are required to be orange). In addition, the addition of carbonizing agents will cause the insulation volume resistivity of the material to decrease.
[0005] 2. Chinese patent CN 109251399B proposes a soft, low-smoke, halogen-free, highly flame-retardant and oil-resistant cable material for in-vehicle high-voltage wires and a preparation method thereof. The oil-resistant material for in-vehicle high-voltage wires, wherein the halogen-free flame retardant is a blend of aluminum diethylphosphinate and aluminum hydroxide in a weight ratio of 3:1; the flame retardant synergist is a silane coupling agent coated with melamine polyphosphate. Aluminum diethylphosphinate is easily hydrolyzed, which can easily cause the insulation resistance of the material to decrease, resulting in a decrease in the protective effect of the cable and inability to operate safely for a long time. In order to improve the softness of the material, a plasticizer is added, which is at least one of trimethylolpropane, diethylene glycol dibenzoate and tri-n-butyl acetyl citrate. Although the introduction of the plasticizer improves the softness of the material, it is easy to cause a significant decrease in the tear resistance of the material, resulting in the risk of cracking of the cable. At the same time, the presence of plasticizers, especially plasticizers containing benzene, is prone to produce volatile odors, which does not meet the requirements. Summary of the invention
[0006] The present invention adopts non-oil-filled SEBS, ethylene-propylene-butylene block copolymer elastomer and polyethylene grafted maleic anhydride compatibilizer as the base resin, wherein:
[0007] SEBS has excellent electrical properties and softness. Generally, SEBS needs to be filled with oil to improve the softness and extrusion processing performance of the material, but the disadvantages of oil filling are also obvious, which will affect the flame retardant properties, tear resistance and crack resistance of the material. This formula uses non-oil-filled SEBS, and when designing other components, it overcomes the shortcomings of material softness and extrusion processing performance caused by non-oil filling.
[0008] Due to its structural characteristics, the ethylene-propylene-butene ternary block copolymer elastomer has a lower hardness. Compared with the EVA and EVM introduced in the prior art for oil resistance, the elastomer has excellent electrical properties. At the same time, its higher melting point enables it to withstand related solvents at a certain temperature.
[0009] Polyethylene grafted with maleic anhydride as a compatibilizer has excellent electrical properties.
[0010] In the present invention, low melt index high density polyethylene is selected as the compatibilizer matrix resin. The polyethylene has a high density and significantly improves the chemical solvent resistance. The high density polyethylene has the characteristics of high crystallinity and large molecular weight. While meeting the chemical solvent resistance, the mechanical and tear resistance properties are improved.
[0011] Compared with the conventional silane coupling agent modified powder solution, phosphorus-containing silane forms phosphorus-containing free radicals during the combustion process, which can quench free radicals, terminate the combustion reaction, and improve the flame retardant properties of the material. On this basis, polycarbosilane is further introduced as a synergistic flame retardant to further improve the flame retardant properties of the material. The material can meet the relevant flame retardant requirements under the premise of lower flame retardant filling, reducing the impact and degradation on the material's softness, tear resistance and other related properties.
[0012] In addition, for radiation cross-linked materials, the present invention adopts a 5-functional group or 6-functional group cross-linking sensitizer to replace the traditional 2-functional group sensitizer (such as TAIC, TAC, TMPTMA, etc.). The increase in the functional groups of the sensitizer can significantly improve the radiation cross-linking efficiency of the material. Under compatible radiation doses, while ensuring the cross-linking degree of the material, the damage of the radiation rays to the main chain of the matrix resin macromolecule is reduced. On the one hand, it can reduce the decrease in tear resistance caused by radiation, and on the other hand, it can reduce the influence of radiation on flame retardancy.
[0013] Advantages of the invention:
[0014] A soft high-melting-point elastomer is blended with a polyethylene resin with a high degree of crystallinity to replace the low-melting-point polar polymers EVA and EVM in traditional solutions. This solves the problem of chemical solvent resistance of automotive cable materials while reducing the impact of polar resins on the electrical properties of insulating materials, avoiding leakage or short circuit problems caused by decreased insulation performance.
[0015] Compared with traditional non-phosphorus-based silanes, such as vinyl silane surface-modified aluminum hydroxide, the use of phosphorus-based silanes can achieve excellent flame retardancy and carbonization with a better flame retardant dosage, further improving the softness of the material. In addition, compared with the commonly used magnesium hydroxide / hydromagnesium / aluminum hydroxide flame retardant system, in order to meet the softness of the material, it is generally necessary to introduce additional flame retardant synergists, such as aluminum hypophosphite and carbon-forming agents. Aluminum hypophosphite is easy to absorb moisture, and its acidic characteristics also affect extrusion processing. Commercial carbon-forming agents are generally modified by intercalation of a large amount of organic solvents, which are very easy to dilute and affect the electrical insulation properties of the material. The volatilization of organic solvents during use in high-temperature environments will accelerate the aging of the material and affect its service life.
[0016] In order to further improve the softness of the material, improve the tear resistance, and meet the flame retardant performance under low flame retardant filling conditions, polycarbosilane and aluminum hydroxide are introduced for synergistic flame retardancy. At the same time, for irradiated materials, 5 or 6 functional cross-linking sensitizers are used to replace traditional 2 functional cross-linking sensitizers to improve cross-linking efficiency and cross-linking density, and improve the tear resistance and flame retardant properties of the material.
[0017] A method for preparing a low-smoke, halogen-free, flame-retardant polyolefin insulation material for an in-vehicle high-voltage cable comprises: firstly, weighing raw materials according to a formula, and then preparing the material according to the following steps:
[0018] S1, using phosphorus-containing silane to modify aluminum hydroxide powder and perform surface treatment.
[0019] S2, feeding the base resin into a high-speed mixer and mixing it evenly;
[0020] S3, using a large aspect ratio twin-screw extruder to blend and granulate the material obtained in step S2;
[0021] S4, the material obtained in step S3, the material obtained in step S1 and other raw materials are put into an internal mixer, and a finished product is prepared by an internal mixer plus a two-stage production granulation process.
[0022] In step S1, the aluminum hydroxide powder is first preheated to 80-90° C., the powder is fully stirred, and during the stirring process, the phosphorus-containing silane aerosol is sprayed onto the surface of the powder.
[0023] In step S3, the aspect ratio of the twin-screw extruder is ≥52, and the base resin is pre-mixed and granulated using a twin-screw with a large aspect ratio. Under a long and sufficient shearing action, the mixture forms a nearly homogeneous system, and good dispersibility makes the material performance better. DETAILED DESCRIPTION
[0024] The present invention is further described below in conjunction with specific embodiments.
[0025] (1) Formula composition
[0026] According to mass fraction, including
[0027] SEBS 30-50 parts,
[0028] 30-50 parts of ethylene-propylene-butylene block copolymer elastomer,
[0029] 10-20 parts of polyethylene grafted maleic anhydride compatibilizer,
[0030] 3-5 parts of masterbatch,
[0031] 1.5-2.5 parts of antioxidant,
[0032] 110-130 parts of aluminum hydroxide,
[0033] Silane 1.5-3 parts,
[0034] 3-5 parts of polycarbosilane,
[0035] 1-2 parts of cross-linking agent,
[0036] 3-5 parts of silicone masterbatch.
[0037] in:
[0038] SEBS is in the form of non-oil-filled granules.
[0039] The polyethylene substrate used in the polyethylene grafted maleic anhydride compatibilizer is high-density polyethylene.
[0040] The antioxidant is (commercially available from BASF) antioxidant B255 (pentaerythritol tetrakis[β-(3,5-di-tert-butyl-4-hydroxyphenyl) propionate) or B900 (tris(2,4-di-tert-butylphenyl) phosphite). B225 is a compound of antioxidant 1010 and antioxidant 168 in a ratio of 1:1. B900 is a compound of antioxidant 1076 and antioxidant 168 in a ratio of 1:4.
[0041] The silane is a phosphorus-containing silane (such as 3-(trihydroxysilyl)propylmethyl phosphate or tris(trimethylsilyl)phosphate).
[0042] The cross-linking agent has a 5-functional structure (such as dipentaerythritol pentaacrylate DPEPA) or a 6-functional structure (such as dipentaerythritol hexaacrylate DPHA).
[0043] (2) Prepare insulating material according to the formula
[0044] Firstly, phosphorus-containing silane is used to modify aluminum hydroxide and perform surface treatment.
[0045] The aluminum hydroxide powder is preheated to 80-90°C, and the powder is stirred at a stirring speed of 600-800 rpm. During the stirring process, the phosphorus-containing silane is converted from liquid to aerosol through an atomizing device and sprayed onto the powder surface. The spraying and stirring time is 30-50 minutes.
[0046] Then, the base resin (non-oil-filled SEBS, ethylene-propylene-butene block elastomer and polyethylene grafted maleic anhydride compatibilizer as the base resin) is weighed and fed into a high-speed mixer according to the formula ratio; after being mixed evenly, a large aspect ratio twin-screw extruder is used to blend and granulate the base resin to improve the compatibility and dispersibility of the polymer components.
[0047] Temperature settings of each zone of the twin-screw extruder: barrel zone 1: 120±5℃, barrel zone 2: 140±5℃, barrel zone 3: 150±5℃, barrel zone 4: 160±5℃, barrel zone 5: 170±5℃, barrel zone 6: 180±5℃, barrel zone 7: 185±5℃, barrel zone 8: 190±5℃, barrel zone 9: 190±5℃, die head: 190±5℃.
[0048] Next, the material prepared by twin-screw blending is weighed with the modified powder (aluminum hydroxide) and its raw materials according to the ratio and then put into the internal mixer, and the finished material is prepared by internal mixing and two-stage production granulation process.
[0049] In the process of internal mixing and two-stage production granulation:
[0050] The mixing temperature is 150-160℃, the mixing time is 10-20min, the discharge temperature is controlled at 150-160℃, and after mixing, double cone feeding is carried out, and the feeding temperature is 80-90℃;
[0051] The temperature of each zone of the twin-screw mixing is: 90-100°C in zone 1, 90-100°C in zone 2, 90-100°C in zone 3, 80-90°C in zone 4, 80-90°C in zone 5, 80-90°C in zone 6, and 80-90°C in zone 7. The speed of the twin-screw is 180-230rpm.
[0052] The temperatures of each zone of single screw extrusion are: 95-105°C in zone 1, 105-115°C in zone 2, 115-125°C in zone 3, 120-130°C in zone 4, and 125-130°C in zone 5. The speed of the single screw is 80-100rpm.
[0053] (3) Embodiment
[0054] In this embodiment, a low-smoke, halogen-free, flame-retardant polyolefin insulation material for in-vehicle high-voltage cables is provided, and the raw materials for preparing the insulation material include the following components in parts by weight:
[0055] Example 1
[0056]
[0057]
[0058] Example 2
[0059]
[0060] Example 3
[0061]
[0062] Example 4
[0063]
[0064] Example 5
[0065]
[0066]
[0067] Example 6
[0068]
[0069] Comparative Example 1
[0070] The only difference from Example 1 is that the ethylene-propylene-butene block copolymer elastomer is replaced by POE (ethylene-butene).
[0071] Comparative Example 2
[0072] The only difference from Example 1 is that the silane is replaced by vinyltri(β-methoxyethoxy)silane (A-172).
[0073] Comparative Example 3
[0074] The only difference from Example 1 is that polycarbosilane is replaced by the carbon-forming agent.
[0075] Comparative Example 4
[0076] The only difference from Example 1 is that the high-density polyethylene grafted maleic anhydride compatibilizer is replaced by a commonly used LLDPE-g-MAH compatibilizer.
[0077] The formula table of each embodiment and comparative example is as follows:
[0078]
[0079]
[0080]
[0081] The test results of each embodiment and comparative example are shown in the following table, and the reference test standards are as follows:
[0082] GB / T 1040.3-2006 Determination of tensile properties of plastics Part 3: Test conditions for films and sheets;
[0083] GB / T 1408.1-2016 Test methods for electrical strength of insulating materials Part 1: Tests at power frequency;
[0084] GB / T 2411-2008 Plastics and hard rubber - Determination of indentation hardness (Shore hardness) using a durometer;
[0085] GB / T 2951.12-2008 General test methods for insulation and sheath materials of electric and optical cables Part 12: General test methods - Thermal aging test methods;
[0086] GB / T 2951.14-2008 General test methods for insulating and sheathing materials of electric and optical cables Part 14: General test methods - Low temperature tests;
[0087] GB / T 5470-2008 Test method for impact embrittlement temperature of plastic insulation;
[0088] GB / T 17650.1-1998 Test method for gases released during combustion of materials of electric or optical cables Part 1: Determination of the total amount of halogen acid gases;
[0089] GB / T 17650.2-1998 Test methods for gases released during combustion of materials of electric or optical cables Part 2: Determination of the acidity of the gas by measuring pH value and conductivity;
[0090] GB / T 25085-2010 60V and 600V single-core wires for road vehicles;
[0091] GB / T 31838.2-2019 Dielectric and resistive properties Part 2: Resistive properties (DC method) Volume resistance and volume resistivity.
[0092]
[0093]
[0094] In the present invention, a high melting point elastomer is selected to replace the traditional EVA and EVM. The elastomer has excellent electrical properties, and its high melting point enables it to withstand relevant solvents at a certain temperature.
[0095] Low melt index high-density polyethylene is selected as the compatibilizer base resin. The polyethylene has a high density and significantly improves the chemical solvent resistance. The high crystallinity and large molecular weight of high-density polyethylene are used to meet the chemical solvent resistance while improving the mechanical and tear resistance. Compared with comparative example 1, the chemical solvent resistance of Example 1 is significantly improved, and the mechanical properties and tear resistance are also improved.
[0096] Compared with the conventional silane coupling agent modified powder solution, the phosphorus-containing silane forms phosphorus-containing free radicals during the combustion process, which can quench the free radicals, terminate the combustion reaction, and improve the flame retardant properties of the material. Compared with Comparative Example 2, the UL94 combustion grade of Example 1 is significantly improved.
[0097] On this basis, polycarbosilane is further introduced as a synergistic flame retardant to further improve the flame retardant properties of the material. The material can meet the relevant flame retardant requirements under the premise of lower flame retardant filling, reducing the impact and degradation on the material's softness, tear resistance and other related properties. Compared with comparative example 3, the UL94 and smoke density of Example 1 are significantly improved. At the same time, compared with the conventional carbon-forming agent system, the electrical properties of the material are more excellent, and the impact on the material's tear resistance is smaller.
[0098] In addition, for radiation cross-linked materials, the present invention adopts 5-functional group and 6-functional group cross-linking sensitizers to replace traditional 2-functional group sensitizers (such as TAIC, TAC, TMPTMA, etc.). The increase in the functional groups of the sensitizer can significantly improve the radiation cross-linking efficiency of the material. Under compatible radiation doses, while ensuring the cross-linking degree of the material, the damage of the radiation rays to the main chain of the matrix resin macromolecule is reduced. On the one hand, it can reduce the decrease in tear resistance caused by radiation, and on the other hand, it can reduce the influence of radiation on flame retardancy.
Claims
1. A low-smoke, halogen-free, flame-retardant polyolefin insulation material for in-vehicle high-voltage cables, characterized in that The raw materials include by weight: SEBS 30-50 parts, 30-50 parts of ethylene-propylene-butylene block copolymer elastomer, 10-20 parts of polyethylene grafted maleic anhydride compatibilizer, 3-5 parts of masterbatch, 1.5-2.5 parts of antioxidant, 110-130 parts of aluminum hydroxide, 1.5 to 3 parts of phosphorus-containing silane, 1-2 parts of cross-linking agent, 3-5 parts of silicone masterbatch; Wherein: SEBS, ethylene-propylene-butylene block copolymer elastomer and polyethylene grafted maleic anhydride compatibilizer are used as base resin; SEBS is in oil-free granular form; The aluminum hydroxide is in powder form and is modified by phosphorus-containing silane; The crosslinking agent is a multifunctional crosslinking sensitizer, and the functional groups are not less than 2.
2. The low-smoke, halogen-free, flame-retardant polyolefin insulation material for in-vehicle high-voltage cables according to claim 1 is characterized in that It also includes 3 to 5 parts of polycarbosilane.
3. The low-smoke, halogen-free, flame-retardant polyolefin insulation material for in-vehicle high-voltage cables according to claim 1 is characterized in that The crosslinking agent is a crosslinking sensitizer with a 5-functional group structure or a crosslinking sensitizer with a 6-functional group structure.
4. The low-smoke, halogen-free, flame-retardant polyolefin insulation material for in-vehicle high-voltage cables according to claim 1 is characterized in that The polyethylene grafted maleic anhydride compatibilizer is a high-density polyethylene grafted maleic anhydride compatibilizer whose polyethylene substrate is high-density polyethylene.
5. The low-smoke halogen-free flame-retardant polyolefin insulation material for in-vehicle high-voltage cables according to claim 1 is characterized in that the antioxidant is a compound of antioxidant 1010 and antioxidant 168 in a ratio of 1:1, or a compound of antioxidant 1076 and antioxidant 168 in a ratio of 1:
4.
6. The low-smoke, halogen-free, flame-retardant polyolefin insulation material for in-vehicle high-voltage cables according to claim 1 is characterized in that The phosphorus-containing silane is 3-(trihydroxysilyl)propylmethyl phosphate or tris(trimethylsilyl)phosphate).
7. A method for preparing a low-smoke, halogen-free, flame-retardant polyolefin insulation material for in-vehicle high-voltage cables, characterized in that first, raw materials are weighed according to a formula, and then prepared according to the following steps: S1, using phosphorus-containing silane to modify aluminum hydroxide powder and perform surface treatment; S2, feeding the base resin into a high-speed mixer and mixing it evenly; S3, using a large aspect ratio twin-screw extruder to blend and granulate the material obtained in step S2; S4, the material obtained in step S3, the material obtained in step S1 and other raw materials are put into an internal mixer, and a finished product is prepared by an internal mixer plus a two-stage production granulation process.
8. The preparation method according to claim 7, characterized in that in step S1, the aluminum hydroxide powder is first preheated to 80-90°C, the powder is fully stirred, and during the stirring process, the phosphorus-containing silane aerosol is sprayed onto the surface of the powder.
9. The preparation method according to claim 7, characterized in that In step S3, the temperature settings of each zone of the twin-screw extruder are: barrel zone 1: 120±5°C, barrel zone 2: 140±5°C, barrel zone 3: 150±5°C, barrel zone 4: 160±5°C, barrel zone 5: 170±5°C, barrel zone 6: 180±5°C, barrel zone 7: 185±5°C, barrel zone 8: 190±5°C, barrel zone 9: 190±5°C, and head: 190±5°C.
10. The preparation method according to claim 7, characterized in that In the banburying plus two-stage production granulation process of step S4: The mixing temperature is 150-160℃, the mixing time is 10-20min, the discharge temperature is controlled at 150-160℃, and after mixing, double cone feeding is carried out, and the feeding temperature is 80-90℃; The temperature of each zone of the twin-screw mixing is: 90-100°C in zone 1, 90-100°C in zone 2, 90-100°C in zone 3, 80-90°C in zone 4, 80-90°C in zone 5, 80-90°C in zone 6, and 80-90°C in zone 7. The speed of the twin-screw is 180-230rpm. The temperatures of each zone of single screw extrusion are: 95-105°C in zone 1, 105-115°C in zone 2, 115-125°C in zone 3, 120-130°C in zone 4, and 125-130°C in zone 5. The speed of the single screw is 80-100rpm.
Citation Information
Patent Citations
Flexible, low-smoke, halogen-free, flame-retardant, and oil-resistant cable material for high-voltage lines inside vehicles and its preparation method
CN109251399B
Low-smoke halogen-free high-flame-retardant cable material for high-voltage wire in new energy automobile and preparation method thereof
CN117659558A
High flame-retardant and high heat-resisting halogen-free expansion type fire-resistant cable material and preparation method thereof
CN101735546A
Halogen-free flame-retardant polypropylene material for vehicles, and preparation method thereof
CN103396606A
Graphene modified polycarbosilane composite material and preparation method thereof
CN110105771A
Cited By
Preparation method of organic silicon for low-smoke halogen-free wire rod
CN121271146A
Weather-resistant silane crosslinked polyethylene insulated power cable production process
CN121554902A
Production process of weather-resistant silane cross-linked polyethylene insulated power cable
CN121554902B